Bonding property between fiber and cementitious matrix: A critical review. (16th May 2023) - Lin, Chen; Kanstad, Terje; Jacobsen, Stefan; Ji, Guomin
Highlights: Three different bonding mechanisms, including electrostatic attraction bonding, chemical reactions bonding, and mechanical interlocking are illustrated. Commonly used approaches to improve fiber–matrix bonding based on different bonding mechanisms are concluded. Major techniques and models to characterize and describe the Interfacial Transition Zone (ITZ) and bonding between fiber and cementitious matrix are summarized. Abstract: The utilization of fibers plays a crucial role in improving the mechanical performance of cementitious composites. The bridging effect of fiber at the cracked surface provides considerable residual tensile strength for fiber-reinforced concrete (FRC). Generally, the mechanical performance of FRC can be markedly improved when suitable types of fiber and dosage are applied. However, the fiber–matrix interface is a critical parameter to determine the performance of FRC by affecting the stress transferability between fiber and concrete matrix. This paper gives an overview of the bonding property between fiber and cementitious matrix. First, three different bonding mechanisms, including electrostatic attraction bonding, chemical reactions bonding, and mechanical interlocking are illustrated. Then, the commonly used approaches to improve fiber–matrix bonding based on different bonding mechanisms are concluded. Finally, the main techniques and models to characterize and describe the Interfacial Transition Zone (ITZ) and bonding between fiber and cementitious matrix are summarized in this paper.